Group of students wearing masks on the steps of their off-campus apartment - Acosta, Ana Sophia (Tufts Archival Research Center, 2020)
Students Anna Champion, Emma Wolfe, Julia Devlin, and Elyssa Anneser on the steps of their off-campus apartment before taking graduation pictures.